Development of STEM-integrated project-based learning to improve critical thinking skills of senior high school students on environmental change material - Indrasti Indrasti; Paidi Paidi (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
The 21st-century education demands mastery of critical thinking skills to address real-world problems. However, existing learning materials have not yet fully supported the systematic development of these skills. This study aims to develop a Project-Based Learning (PjBL) device integrated with STEM that is valid, practical, and effective in enhancing students’ critical thinking skills on the topic of environmental changes. The learning package was comprehensively developed in the form of a module, an interactive e-worksheet, and assessment instruments based on critical thinking indicators. The research employed a Research and Development (R&D) approach using the ADDIE model. The subjects were grade X high school students. Research instruments included validation sheets, practicality questionnaires, and critical thinking tests. The validation results indicated that the developed product was of very high quality, practical to use, and effective in improving critical thinking skills, achieving an n-gain score of 0.70 (high category). All indicators of critical thinking improved significantly, particularly the inference indicator. These findings confirm that the STEM-integrated PjBL into a comprehensive learning package can serve as a strategic innovation to support the implementation of the Kurikulum Merdeka and strengthen 21st-century biology education that emphasizes problem-solving and contextual learning.Abstrak. Pendidikan abad ke-21 menuntut penguasaan keterampilan berpikir kritis untuk menghadapi permasalahan nyata. Namun, perangkat pembelajaran yang tersedia belum sepenuhnya mendukung pengembangan keterampilan tersebut secara sistematis. Penelitian ini bertujuan mengembangkan perangkat pembelajaran berbasis proyek (PjBL) terintegrasi STEM yang valid, praktis, dan efektif dalam meningkatkan keterampilan berpikir kritis peserta didik pada materi perubahan lingkungan. Perangkat dikembangkan secara komprehensif dalam bentuk modul, lembar kerja peserta didik elektronik interaktif, dan instrumen asesmen berbasis keterampilan berpikir kritis. Metode penelitian menggunakan pendekatan R&D dengan model ADDIE. Subjek penelitian adalah peserta didik kelas X SMA. Instrumen penelitian meliputi lembar validasi, angket kepraktisan, dan tes keterampilan berpikir kritis. Hasil validasi menunjukkan bahwa produk yang dikembangkan memiliki kualitas sangat baik, praktis digunakan, dan efektif meningkatkan keterampilan berpikir kritis dengan n-gain sebesar 0,70 (kategori tinggi). Seluruh indikator berpikir kritis meningkat secara signifikan, terutama pada indikator inference. Temuan ini menegaskan bahwa PjBL yang terintegrasi STEM dalam satu paket pembelajaran yang utuh dapat menjadi inovasi strategis dalam mendukung implementasi Kurikulum Merdeka dan memperkuat pendidikan biologi abad ke-21 yang berorientasi pada pemecahan masalah dan pembelajaran kontekstual.